2014
DOI: 10.1016/j.molcel.2014.09.026
|View full text |Cite
|
Sign up to set email alerts
|

A Role for the Mitochondrial Pyruvate Carrier as a Repressor of the Warburg Effect and Colon Cancer Cell Growth

Abstract: Summary Cancer cells are typically subject to profound metabolic alterations, including the Warburg effect wherein cancer cells oxidize a decreased fraction of the pyruvate generated from glycolysis. We show herein that the mitochondrial pyruvate carrier (MPC), composed of the products of the MPC1 and MPC2 genes, modulates fractional pyruvate oxidation. MPC1 is deleted or underexpressed in multiple cancers and correlates with poor prognosis. Cancer cells re-expressing MPC1 and MPC2 display increased mitochondr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

27
352
4
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 317 publications
(394 citation statements)
references
References 73 publications
(77 reference statements)
27
352
4
3
Order By: Relevance
“…A decrease in MPC activity has been shown to perturb whole body glucose homeostasis through effects on glucose-stimulated insulin secretion (11,12) and gluconeogenesis (13,14). In addition, reduced MPC expression (15,16) and activity (17)(18)(19) has been observed in cancer cells, contributing to the Warburg effect. This favors cell growth and metastasis and promotes the establishment and maintenance of the cancer stem cell compartment (15,16,20).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A decrease in MPC activity has been shown to perturb whole body glucose homeostasis through effects on glucose-stimulated insulin secretion (11,12) and gluconeogenesis (13,14). In addition, reduced MPC expression (15,16) and activity (17)(18)(19) has been observed in cancer cells, contributing to the Warburg effect. This favors cell growth and metastasis and promotes the establishment and maintenance of the cancer stem cell compartment (15,16,20).…”
mentioning
confidence: 99%
“…In addition, reduced MPC expression (15,16) and activity (17)(18)(19) has been observed in cancer cells, contributing to the Warburg effect. This favors cell growth and metastasis and promotes the establishment and maintenance of the cancer stem cell compartment (15,16,20).…”
mentioning
confidence: 99%
“…This conserved protein complex is responsible for transporting pyruvate into the mitochondrial matrix and represents the key metabolic link between glycolysis and oxidative phosphorylation (Bricker et al, 2012). Consistent with Warburg's observations, the Rutter lab found that many cancers exhibit decreased MPC1 expression, which results in an enhanced glycolytic state and increased tumor growth (Schell et al, 2014). Furthermore, Rutter also described unpublished data which reveal that the MPC promotes stem cell proliferation in the intestine, thereby implicating MPC as a key developmental regulator.…”
Section: New Roles For the Warburg Effectmentioning
confidence: 70%
“…Alternative explanations for the effect include decrease pyruvate production by PKM2, upregulated LDH and increase expression of PDH kinase PDK1. Rutter's group now showed that impaired mitochondrial transport due to MPC1 deletion or diminished expression could also explain the Warburg effect [33]. The authors found that while the gene locus of MPC2 is not frequently loss or altered in cancer, the MPC1 locus is within the most frequently deleted region across all cancer samples investigated.…”
Section: Mpc Mitochondrial Pyruvate Transport and Cancermentioning
confidence: 99%